Understanding Riba through Hadith Literature: An Examination of Al-Baqarah 2:275 - Zainuddin (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2025)
ABSTRACT The prohibition of riba constitutes a fundamental principle in Islamic teachings aimed at preserving justice and balance in economic activities. This study examines the interpretive relationship between Q.S. Al-Baqarah (2:275) and several authentic hadiths on riba in order to reconstruct a coherent textual framework. Through qualitative textual analysis of classical tafsir works and major hadith commentaries, the research explores how the Prophetic traditions function to elaborate the actors, mechanisms, and socio-economic consequences involved in riba practices. The findings indicate that the hadith literature operates as an epistemic extension of the Qur’anic prohibition, transforming a general theological warning into a structured legal-ethical system governing economic behavior. This study offers a theoretical contribution to hadith studies by emphasizing the hermeneutical role of hadith in the formation of Islamic economic norms, while also providing conceptual clarification for contemporary debates regarding the relevance of the prohibition of riba within modern financial systems.